1999
DOI: 10.1002/hep.510300617
|View full text |Cite
|
Sign up to set email alerts
|

The human multidrug resistance protein 2 gene: Functional characterization of the 5?-flanking region and expression in hepatic cells

Abstract: The human multidrug resistance protein 2 (MRP2), also termed as the canalicular multispecific organic anion transporter (cMOAT), is a member of the adenosine triphosphate-binding cassette transporter superfamily. In the liver, MRP2 mediates the multispecific efflux of various types of organic anions, including glucuronate, sulfate, and glutathione conjugates, across the canalicular hepatocyte membrane to the bile. To investigate how the MRP2 gene is expressed in liver cells, the 5'-flanking region of the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 30 publications
4
68
1
5
Order By: Relevance
“…Furthermore, heavy metals such as lead, cadmium and mercury may cause an increase in production of reactive oxygen species (ROS) (Ercal et al, 2001) and expression of ABCC2 has been demonstrated to be associated with elevated cellular ROS (Payen et al, 2001). The Nrf2 (nuclear factor-erythroid 2 p45-related factor 2) transcription factor, which binds the ARE sequences (antioxidant-response element; also named electrophile response element, EPRE) and regulates a battery of detoxifying and antioxidant genes in response to oxidative stress (Adachi et al, 2007;Kang et al, 2005) may be involved in the induction of abcc2 gene by these metals, since previous studies have demonstrated the existence of ARE elements in the promoters of human and mouse Abcc2 gene (Tanaka et al, 1999;Vollrath et al, 2006) and the involvement of ARE-Nrf2 pathway in the induction of Abcc2 gene by several xenobiotics (Vollrath et al, 2006). Therefore, it is of great interest to further study mechanisms underlying the tissuespecific expressing and the induction of zebrafish abcc2 gene by mercury and lead.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heavy metals such as lead, cadmium and mercury may cause an increase in production of reactive oxygen species (ROS) (Ercal et al, 2001) and expression of ABCC2 has been demonstrated to be associated with elevated cellular ROS (Payen et al, 2001). The Nrf2 (nuclear factor-erythroid 2 p45-related factor 2) transcription factor, which binds the ARE sequences (antioxidant-response element; also named electrophile response element, EPRE) and regulates a battery of detoxifying and antioxidant genes in response to oxidative stress (Adachi et al, 2007;Kang et al, 2005) may be involved in the induction of abcc2 gene by these metals, since previous studies have demonstrated the existence of ARE elements in the promoters of human and mouse Abcc2 gene (Tanaka et al, 1999;Vollrath et al, 2006) and the involvement of ARE-Nrf2 pathway in the induction of Abcc2 gene by several xenobiotics (Vollrath et al, 2006). Therefore, it is of great interest to further study mechanisms underlying the tissuespecific expressing and the induction of zebrafish abcc2 gene by mercury and lead.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that this CCAAT-box was indeed critical to the mAbcc6 gene expression. Interestingly, the human ABCC1, ABCC2 and the rat Abcc3 genes, which are closely related to ABCC6/Abcc6, are also under the control of TATAless promoters with Sp1 involvement [44][45][46][47][48][49]. However, there are significant differences in the tissue and temporal expression profiles of those genes indicating that the ABCC6/Abcc6 gene expression depends on other transcription factors and/or regulatory mechanisms [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in Dulbecco's modified Eagle's medium (Nissui Seiyaku, Tokyo, Japan) supplemented with 10% fetal calf serum, 0.1 mM nonessential amino acids (Invitrogen, Paisley, UK) in a humidified incubator (5% CO 2 , 37°C). The medium contained 0.292 mg/ml glutamine, 100 mg/ml kanamycin, and 100 units/ml penicillin (41).…”
Section: Methodsmentioning
confidence: 99%
“…RNA samples (15 g/lane) were separated on a 1% formaldehyde-agarose gel and were transferred to a membrane as described by Tanaka et al (41). The membranes were prehybridized and hybridized with ␣-32 P-labeled probes (41).…”
Section: Methodsmentioning
confidence: 99%